Nisekoi : false love. Vol. 18, Attack - Komi, Naoshi, 1986- (Shonen Jump manga., 2016)
"Love triangle! Comedic antics!! Gang warfare?! You wont want to miss out on Shonen Jump's laugh-out-loud feel-good manga series! It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. It 's day three of the school trip, and Raku visits a temple known to be a power spot. Little does he know that its a place famous for magical bows and arrows that have romance-fulfilling properties! With all the girls determined to shoot him down, which huntress will bring down her prey?!"--Pg.4 of cover.